Análise dos efeitos da Terapia de Aceitação e Compromisso em grupo de clientes com dor crônica - Saban, Michaele Terena (2013)
The objective of this study was to analyze the effect of the protocol adaptation "Live with Chronic Pain: An Acceptance-based Approach" (Vowles & Sorrell, 2007), based on Acceptance and Commitment Therapy (1999) in three participants with chronic pain who attended the Rehabilitation Centre and Day Hospital Psychiatry Institute of a public hospital in São Paulo. A multiple baseline design was used, where intervention was initiated to two participants at a time and the last participant to four weeks later. The forms of measurement data were questionnaires (Profile Questionnaire, Questionnaire History of Pain, Brief Pain Inventory, WHOQOL-Brev, HAD Scale and Chronic Pain Acceptance Questionnaire) applied an initial interview, before the intervention, during, and 6-9 weeks follow-up depending on participant; observation time speech of the participants in the session; and an auto registration contingency in which the participant fulfilled when was in pain for a week before the intervention and during the weeks that occurred in the eight sessions. The results demonstrate that the intervention was benefit to participants, particularly in the reduction of pain episodes, reduction of medication use and rest due to pain. Comparing pre-intervention and follow-up, all participants improved in relation to anxiety and social relationships. The auto record was the instrument that yields information about the therapeutic process and was methodologically the most interesting option for measuring in this search